Religion as a coping strategy to climate-induced depressive symptoms among farmers in Yapei in Ghana's Savannah region - Obiri-Yeboah, Sandra; Bekoe, Adolf Awuku; Doe, Eric Kofi (Frontiers in Human Dynamics, 2025)
IntroductionClimate change is increasingly impacting vulnerable populations, with severe effects on livelihoods and mental health. In many African communities, religion plays a vital role in coping with these challenges. However, little is known about how religious beliefs help farmers in impoverished areas manage climate-induced depressive symptoms.MethodsA qualitative design was used to examine how farmers in Yapei, Central Gonja District of Ghana, use religion to cope with climate-induced depressive symptoms. Data collection comprised 20 in-depth interviews and four focus group discussions (n = 40), involving participants who had experienced climate-related livelihood disruptions.ResultsParticipants reported depressive symptoms, such as inability to sleep (insomnia), think clearly, appetite loss, and suicidal thoughts, due to flooding and drought-related livelihood disruptions. These symptoms were reported by both male (75%) and female (25%) participants. Despite these challenges, participants turned to religious beliefs and practices for relief. Faith and belief in God for divine intervention were central to managing these depressive symptoms.DiscussionThe findings highlight religion as a crucial coping strategy for the mental health impacts of climate change. Faith provided psychological relief and a sense of hope amid adversity.